A new early hominin calcaneus from Kromdraai (South Africa). Issue 2 (4th April 2022) - Harper, Christine M.; Zipfel, Bernhard; DeSilva, Jeremy M.; McNutt, Ellison J.; Thackeray, Francis; Braga, José
Abstract: The Kromdraai site in South Africa has yielded numerous early hominin fossils since 1938. As a part of recent excavations within Unit P, a largely complete early hominin calcaneus (KW 6302) was discovered. Due to its role in locomotion, the calcaneus has the potential to reveal important form/function relationships. Here, we describe KW 6302 and analyze its preserved morphology relative to human and nonhuman ape calcanei, as well as calcanei attributed to Australopithecus afarensis, Australopithecus africanus, Australopithecus sediba, Homo naledi, and the Omo calcaneus (either Paranthropus or early Homo ). KW 6302 calcaneal morphology is assessed using numerous quantitative metrics including linear measures, calcaneal robusticity index, relative lateral plantar process position, Achilles tendon length reconstruction, and a three‐dimensional geometric morphometric sliding semilandmark analysis. KW 6302 exhibits an overall calcaneal morphology that is intermediate between humans and nonhuman apes, although closer to modern humans. KW 6302 possesses many traits that indicate it was likely well‐adapted for terrestrial bipedal locomotion, including a relatively flat posterior talar facet and a large lateral plantar process that is similarly positioned to modern humans. It also retains traits that indicate that climbing may have remained a part of its locomotor repertoire, such as a relatively gracile tuber and a large peroneal trochlea. Specimens from Kromdraai have been attributed to either Paranthropus robustus or early Homo ; however, there are no definitively attributed calcanei for either genus, making it difficult to taxonomically assign this specimen. KW 6302 and the Omo calcaneus, however, fall outside the range of expected variation for an extant genus, indicating that if the Omo calcaneus was Paranthropus, then KW 6302 would likely be attributed to early Homo (or vice versa). Abstract : A new early hominin calcaneus (KW 6302) that exhibits a mix of modern human and nonhuman ape morphologies was found within Unit P at the Kromdraai site (South Africa). Its suite of morphological characteristics indicates that it was well‐adapted for terrestrial bipedalism, but that climbing remained a part of its locomotor repertoire. Previous Kromdraai specimens have been attributed to either Paranthropus robustus or early Homo and while no early hominin calcanei have been definitively attributed to either genus, the Omo calcaneus (either Paranthropus or early Homo ) falls outside of the range of expected variation for an extant genus with KW 6302, indicating that if one specimen is Paranthropus than the other may be early Homo.